Auditor Reputation vs Governance: What Drives Audit Quality in Indonesia’s Transportation & Logistics Sector (2020–2024)? - Setyorini Yuliati; Harti Budi Yanti (Politeknik Ganesha Medan, 2026)
Audit quality is an essential factor that affects financial reporting, especially among emerging markets, including sectors that belong to risky industries, such as transportation and logistics. This research aims to investigate several factors, such as auditor gender, audit firm reputation, and audit committee activities, that affect audit quality, especially for companies listed on the Indonesia Stock Exchange that belong to the transportation and logistics industry. This research used balanced panel data that includes companies from 2020 to 2024, where audit quality is measured according to discretionary accrual figures from Modified Jones Model regression including control variables for firm sizes, leverage, and profitability. Audit committee is found to have a positive and significant correlation with discretionary accrual figures, indicating lower audit quality while auditor gender and audit firm reputation have no relationship with audit quality. The research also finds profitability to be positively related with audit quality, whereas firm size and leverage were not related to audit quality. The research contributes to audit quality in terms of emerging economies, considering specific studies in Indonesian transportation and logistical companies, utilizing discrete accrual modelling, which represents earnings management signals to proxy audit quality. Practically, the findings imply that regulators, audit firms, and issuers should place greater emphasis on the effectiveness of governance mechanisms rather than relying on audit firm reputation or individual auditor characteristics as signals of better audit quality.